Analisis Tingkat Kemandirian Keuangan Badan Layanan Umum Daerah (BLUD) pada RSUD Toto Kabila - Titan Ngabito; Saprudin Saprudin; Novaliastuti Masiaga; Silviana Taniu; Mohamad Abdul Radjak Masjhur (AKUNTANSI 45, 2025)
The implementation of Regional Public Service Agencies (BLUD) in public hospitals is a response to the demands of public sector reform that call for efficiency, accountability, and improvement in the quality of health services. This study aims to analyze the financial independence level of RSUD Toto Kabila as one of the hospitals that has implemented the BLUD system in Bone Bolango Regency. The research was conducted using a quantitative approach through financial independence ratio analysis based on budget realization report data for the period 2014–2023. The results show that the financial independence level of RSUD Toto Kabila tends to increase year by year, but still shows dependence on government funding, especially in the early phases of BLUD implementation. Nevertheless, the trend of the hospital's original income growth indicates that efforts to improve efficiency and management based on good governance principles are starting to yield positive results. This finding indicates that the financial management flexibility provided through the BLUD status can encourage an increase in financial autonomy of hospitals if supported by adaptive managerial strategies and sound financial planning. This research contributes to the understanding of the effectiveness of the BLUD model in the context of strengthening the financial independence of regional hospitals and suggests the need to enhance managerial capacity and internal oversight to maintain the principles of accountability and transparency